A case of occult pancreaticobiliary reflux due to endoscopically confirmed relaxation of the Oddi sphincter. Issue 1 (26th September 2022) - Kataoka, Fumiya; Miura, Shin; Kume, Kiyoshi; Kikuta, Kazuhiro; Hamada, Shin; Takikawa, Tetsuya; Matsumoto, Ryotaro; Ikeda, Mio; Sano, Takanori; Sasaki, Akira; Masamune, Atsushi
Abstract: An otherwise healthy 45‐year‐old woman had been experiencing intermittent right upper abdominal pain for the past 1 year. Computed tomography showed pneumobilia and pancreatic duct emphysema despite a normal duodenal papilla. Magnetic resonance cholangiopancreatography and endoscopic ultrasound confirmed bile duct dilation but without a pancreaticobiliary maljunction. Duodenoscopy detected a slightly sunken, unfixed, and spontaneously enlarged duodenal papilla. During the cholangiogram, the Oddi sphincter was relaxed and the catheter could be easily inserted into the bile duct. Further, no findings suggestive of pancreaticobiliary maljunction were observed, and the contrast medium leaked spontaneously from the duodenal papilla. As biliary amylase level was high, we surmised the occurrence of occult pancreaticobiliary reflux due to relaxation of the Oddi sphincter. However, as there are no guidelines on the management of this condition, we did not offer any treatment. Nevertheless, the patient continued to experience similar symptoms and was retested 1 year later with similar results. As occult pancreaticobiliary reflux was reconfirmed, we suggested that the patient undergo laparoscopic extrahepatic bile duct resection and cholecystectomy, which is the standard treatment for pancreaticobiliary maljunction. Pathological evaluation revealed fibrous thickening of the bile duct wall and chronic cholecystitis, which are typical findings of pancreaticobiliary reflux. Even though pancreaticobiliary reflux is mainly observed in pancreaticobiliary maljunction, it has also been reported in normal patients. Here, we describe a novel mechanism of pancreaticobiliary reflux, namely, a relaxed or defective Oddi sphincter.